INTEGRASI KURIKULUM ISMUBA DALAM MEMBENTUK ETOS KERJA PROFESIONAL SISWA: STUDI KASUS DI SMK MUHAMMADIYAH TASIKMALAYA - Andri Iskandar; Tanto Aljauharie Tantowie (As-Sulthan Journal of Education, 2026)
This study aims to explore the mechanism of the integration of the Al-Islam, Kemuhammadiyahan, and Arabic Language (ISMUBA) curriculum in shaping the professional work ethic of students at SMK Muhammadiyah Tasikmalaya. The main challenge for vocational school graduates today is the need for moral integrity and a work ethic that aligns with the demands of the industrial world. This study uses a descriptive qualitative approach with a field study method. Data were collected through in-depth interviews, observations, and documentation with research subjects including the Principal and Islamic Religious Education (PAI) teachers. The results show that the integration of the ISMUBA curriculum is implemented as a "spirit" that animates technical competencies through the synchronization of theological values ​​​​with vocational practices. The formation of students' professional character is strengthened through spiritual habituation programs such as One Day Five Ayat (ODFA) to train accuracy, Duha Prayer for discipline, and Al-Islam Development Night (MPA) to organize work intentions as worship. In addition, students' independence and social intelligence are developed through the activities of the Autonomous Organization (Ortom) and the Lazismu Infaq Movement. This synergy has proven effective in producing graduates who are not only technically competent, but also possess strong moral integrity in accordance with the vision of "Progressive Islam".